Computation of stability derivative for a wing for specific heat ratio= 1.66 for hypersonic flow - SHAMITHA, A; Crasta, Asha; Khan, Sher Afghan; VASAVI, P (TJPRC Pvt. Ltd, 2020)
The flight performance of aircraft relies on aerodynamic non-dimensional parameters like the drag coefficient, lift coefficient, and the moment coefficient of the aerospace vehicles. The knowledge of these properties is supremely necessary for optimal design, and thus the aerodynamics and the performance of the aerospace vehicles are characterized so as to relate general airplane design and performance to a standard ballistic atmosphere as the reference for all the computations while evaluating the dynamics and control. Since re-entry includes movement through the atmosphere, the entry performance relies on the ambient atmospheric properties. Air under normal conditions behaves very much like a perfect gas. The specific heat ratio for the air as the perfect gas is 1.4. This study focuses attention on variations on γ while the stability derivatives are computed, one such endeavor is made to study the stability derivatives of the wing for γ=1.66. The results show a reduction in its numerical value with k, the level of inertia, and an increment when the angle of incidence increases, leading to a substantial change in the numerical value. At Lower Mach numbers, a considerable change in magnitude for stability derivatives has been observed, but for higher Mach numbers, the change is negligible, thus holding the Mach number Independence principle. As regards the change in the Damping derivative at various pitching locations, at first, its value decreases attain a minimum value, which is the location of the center of pressure, and after that shows a sudden increase. Further, when the  value is varied from 1.4 to 1.66, a difference of 20% in magnitude is observed in the stability derivatives. Flow considered is non-viscous and quasi-steady.